Shatterproof adhesive sheet and display

The integration of a colored shatter-proof adhesive sheet on the protective panel of a display body addresses the issues of design unity and panel fragmentation, enhancing both design aesthetics and safety.

JP7671706B2Active Publication Date: 2025-05-02LINTEC CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022019059
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-02-09
Publication Date
2025-05-02
Estimated Expiration
2040-03-11

AI Technical Summary

Technical Problem

Existing display technologies struggle to provide a unified design with surrounding members and fail to enhance designability, while also lacking effective solutions to prevent the scattering of broken protective panels in display bodies.

Method used

A shatter-proof adhesive sheet with a colored adhesive layer is applied to the protective panel of a display body, enhancing exterior harmony with peripheral members and preventing the scattering of broken panel fragments.

Benefits of technology

The solution improves the design of the display body by achieving exterior harmony with the frame material and printed layers, while also effectively preventing the scattering of broken panel fragments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671706000004
    Figure 0007671706000004
  • Figure 0007671706000005
    Figure 0007671706000005
  • Figure 0007671706000006
    Figure 0007671706000006
Patent Text Reader

Abstract

To provide a shatterproof adhesive sheet capable of improving the design of a display, and a display having improved design. [Solution] A shatterproof adhesive sheet 1 is provided on at least one side of a protective panel 2 used in a display, the shatterproof adhesive sheet 1 comprising a substrate 11 and a colored adhesive layer 12. The shatterproof adhesive sheet 1 preferably has a lightness L* defined by the CIE1976 L*a*b* color system of 92 or less, a total image clarity of optical combs of 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm, and 2.0 mm measured in accordance with JIS K7374:2007 of 400 or more, and a total light transmittance of 5% or more and 95% or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a shatterproof adhesive sheet provided on at least one surface side of a protective panel used in a display, and to a display provided with the shatterproof adhesive sheet. [Background technology]

[0002] In recent years, display devices such as liquid crystal display devices and organic electroluminescence devices are increasingly being used in display devices (displays), for example, in-vehicle displays such as automobile instrument panels, car navigation systems, and various instruments provided in consoles, displays such as tablet terminals for general users, displays such as commercial tablet terminals and digital signage, and displays such as outdoor digital signage.

[0003] As described above, in indicators for in-vehicle use and the like, when the indicator is turned off, it is sometimes required to improve the design by creating a sense of unity with the surrounding members of the indicator, for example, the frame member. To achieve this, it is conceivable to color the indicator, and for example, Patent Documents 1 to 4 disclose inventions related to coloring of indicators. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2000-313871 A [Patent Document 2] JP 2009-188298 A [Patent Document 3] JP 2012-234028 A [Patent Document 4] JP 2017-57375 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, the techniques disclosed in the above Patent Documents 1 to 4 all have different purposes for coloring, and therefore could not provide a sense of unity between the display body and surrounding members and improve the design.

[0006] On the other hand, there is a problem that the protective panel breaks and the fragments scatter when a display for mobile use receives a large impact due to a fall, etc., or when a display for vehicle use receives a large impact due to an accident, etc. For this reason, it has been proposed to attach a shatterproof adhesive sheet to the protective panel to prevent the shattered protective panel from scattering.

[0007] The present invention has been made in consideration of the above-mentioned circumstances, and aims to provide a shatterproof adhesive sheet that can improve the design of a display body, and a display body with improved design. [Means for solving the problem]

[0008] In order to achieve the above-mentioned object, firstly, the present invention provides a shatterproof adhesive sheet to be provided on at least one side of a protective panel used in a display device, the shatterproof adhesive sheet being characterized by comprising a substrate and a colored adhesive layer (Invention 1).

[0009] The shatterproof adhesive sheet according to the above invention (Invention 1) has a colored adhesive layer, and by providing the shatterproof adhesive sheet on at least one side of a protective panel, the resulting display body can, for example, have a good appearance harmony with surrounding components such as the frame material of the display body when the light is turned off, a frame-shaped printed layer, a printed layer showing characters and symbols, etc., thereby improving the design. Furthermore, even if the protective panel is cracked due to impact or the like, the shattered protective panel is prevented from scattering because the shatterproof adhesive sheet is attached to the protective panel.

[0010] In the above invention (Invention 1), it is preferable that the lightness L* defined by the CIE1976 L*a*b* color system is 92 or less (Invention 2).

[0011] In the above inventions (Inventions 1 and 2), it is preferable that the total value of image clarity of optical combs of 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm and 2.0 mm measured in accordance with JIS K7374:2007 is 400 or more (Invention 3).

[0012] In the above inventions (Inventions 1 to 3), the total light transmittance is preferably 5% or more and 95% or less (Invention 4).

[0013] In the above inventions (Inventions 1 to 4), the adhesive constituting the colored adhesive layer preferably contains a colorant (Invention 5).

[0014] In the above inventions (Inventions 1 to 5), the substrate is preferably a plastic film having a functional layer (Invention 6).

[0015] Secondly, the present invention provides a display device having a protective panel, characterized in that the shatterproof adhesive sheet (Inventions 1 to 6) is provided on one or both sides of the protective panel (Invention 7).

[0016] In the above invention (Invention 7), it is preferable that a frame material is provided on the periphery (Invention 8).

[0017] In the above inventions (Inventions 7 and 8), it is preferable that a print layer is formed on a part of one of the display body constituent members that constitutes the display body (Invention 9). Effect of the Invention

[0018] The shatterproof adhesive sheet according to the present invention can improve the design of a display body. Furthermore, the design of the display body according to the present invention is improved by the shatterproof adhesive sheet. [Brief description of the drawings]

[0019] [Figure 1] 1 is a cross-sectional view of a shatterproof adhesive sheet according to one embodiment of the present invention. [Diagram 2]1 is a cross-sectional view of a display according to an embodiment of the present invention. [Diagram 3] FIG. 11 is a cross-sectional view of a display according to another embodiment of the present invention. [Figure 4] FIG. 2 is a plan view of a display having a frame material according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Hereinafter, an embodiment of the present invention will be described. [Shatterproof adhesive sheet] The shatterproof adhesive sheet according to one embodiment of the present invention is provided on at least one side of a protective panel used in a display body, and includes a substrate and a colored adhesive layer. Details of the display body and the protective panel will be described later.

[0021] Since the shatterproof adhesive sheet according to this embodiment has a colored adhesive layer as described above, by providing the shatterproof adhesive sheet on at least one side of the protective panel, the resulting display body can have a good appearance harmony with surrounding members such as the frame material of the display body when the light is turned off, a frame-shaped printed layer, a printed layer showing characters and symbols, etc., thereby improving the design. Furthermore, even if the protective panel is cracked due to an impact or the like, the shattered protective panel is prevented from scattering because the shatterproof adhesive sheet is attached to the protective panel.

[0022] The lightness L* of the shatterproof adhesive sheet as defined by the CIE1976 L*a*b* color system is preferably 92 or less, more preferably 86 or less, particularly preferably 83 or less, and even more preferably 80 or less. This allows the display to have a sense of unity with the black frame material and printed layer when the display is turned off, improving the harmony of the appearance.

[0023] On the other hand, from the viewpoint of improving the design by the appearance harmony and the visibility of the display, the lower limit value of the lightness L* is preferably 10 or more, more preferably 20 or more, particularly preferably 40 or more, further preferably 50 or more, and most preferably 60 or more. The method of measuring the lightness L*, chromaticity a* and b* defined by the CIE1976 L*a*b* color system in this specification is as shown in the test examples described later.

[0024] The shatterproof pressure-sensitive adhesive sheet preferably has a chromaticity a* defined by the CIE1976 L*a*b* color system of -20 to 20, more preferably -10 to 10, particularly preferably -5 to 5, further preferably -2 to 2, and most preferably -1.5 to 1.5. Having a chromaticity a* within the above range improves the visibility of the display and further improves the design, particularly the appearance harmony of an in-vehicle display.

[0025] Furthermore, the chromaticity b* of the shatterproof pressure-sensitive adhesive sheet, as defined by the CIE1976 L*a*b* color system, is preferably -20 to 20, more preferably -10 to 10, particularly preferably -5 to 5, further preferably -2 to 2, and most preferably -1.2 to 1.2. By having the chromaticity b* within the above range, the visibility of the display body is improved, and the design, particularly the appearance harmony of the display body for vehicle mounting, is further improved.

[0026] The total value of image clarity (%) of optical combs of 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm and 2.0 mm measured in accordance with JIS K7374:2007 for the shatterproof adhesive sheet according to this embodiment (not including the release sheet) is preferably 400 or more, more preferably 405 or more, particularly preferably 410 or more, and even more preferably 415 or more. This makes the visibility of images and videos on the resulting display good. In particular, even if the lightness L* is within the above-mentioned range, the visibility of images and videos on the display is maintained good.

[0027] On the other hand, the total value of the image clarity (%) is preferably not more than 500, more preferably not more than 450, particularly preferably not more than 430, and further preferably not more than 420. This makes it easier for the lightness L* to fall within the above-mentioned range while maintaining good visibility of images and videos on the display.

[0028] Here, the image clarity is measured by passing the amount of parallel light rays transmitted through a test specimen through an optical comb having a transmitting portion and a light-shielding portion. The smaller the width (comb width) between the transmitting portion and the light-shielding portion of the optical comb, the higher the image clarity. The image clarity is measured according to the transmission method of JIS K7374:2007. The specific measurement method is as shown in the test example described later.

[0029] The total light transmittance of the shatterproof adhesive sheet (not including the release sheet) according to the present embodiment is preferably 5% or more, more preferably 20% or more, particularly preferably 30% or more, and even more preferably 40% or more. This improves the visibility of images and videos in the obtained display, and in particular, the boundary between the black display part and the part other than the black display part when the obtained display is turned on can be prevented from becoming unclear. The upper limit of the total light transmittance is not particularly limited, but is usually 100% or less, and considering the relationship with the above-mentioned lightness L*, it is preferably 95% or less, and considering the blackness imparting property in the black display part of the display, it is more preferably 85% or less, particularly preferably 75% or less, and even more preferably 65% ​​or less, and most preferably 60% or less. The total light transmittance in this specification is a value measured in accordance with JIS K7361-1:1997.

[0030] In addition, the degree of coloring (coloring concentration distribution) in the shatterproof adhesive sheet (colored adhesive layer) according to the present embodiment is preferably uniform in the surface direction, which improves the design (particularly the appearance harmony) and visibility of the display.

[0031] A specific configuration of one example of the shatterproof adhesive sheet according to this embodiment is shown in Fig. 1. As shown in Fig. 1, the shatterproof adhesive sheet 1 is composed of a substrate 11, a colored adhesive layer 12 laminated on one side of the substrate 11, and a release sheet 13 laminated on the side of the colored adhesive layer 12 opposite the substrate 11. The colored adhesive layer 12 is in contact with the release surface of the release sheet 13. In this specification, the release surface of the release sheet refers to the surface of the release sheet that has releasability, and includes both a surface that has been subjected to a release treatment and a surface that exhibits releasability even without being subjected to a release treatment.

[0032] 1. Each component 1-1. Base material The substrate 11 may be made of any material having sufficient strength to prevent scattering of the broken protective panel (glass or plastic fragments) when the protective panel of the adherend is broken. The substrate 11 is usually mainly made of a plastic film, and may be made of only a plastic film, or may be a plastic film on which a desired functional layer is formed.

[0033] Examples of the plastic film include polyester films such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate, polyurethane films, polyethylene films, polypropylene films, cellulose films such as triacetyl cellulose, polyvinyl chloride films, polyvinylidene chloride films, polyvinyl alcohol films, ethylene-vinyl acetate copolymer films, polystyrene films, polycarbonate films, acrylic resin films, norbornene-based resin films, and cycloolefin resin films; and laminates of two or more of these. The plastic film may be uniaxially or biaxially stretched.

[0034] Among the above plastic films, so-called optical films are preferred, and specifically, plastic films with a haze value of less than 1% are preferred. If the haze value is less than 1%, the visibility of the resulting display body will be better. As such optical films, polyethylene terephthalate, triacetyl cellulose film, polycarbonate film, cycloolefin resin film, etc. are preferred.

[0035] Furthermore, in the above-mentioned plastic film, in order to improve the adhesion with the layer (colored adhesive layer 12, functional layer, etc.) laminated on the surface, one or both sides may be subjected to a surface treatment such as a primer treatment, an oxidation method, a roughening method, etc. Examples of the oxidation method include corona discharge treatment, chromic acid treatment, flame treatment, hot air treatment, ozone / ultraviolet light treatment, etc., and examples of the roughening method include sandblasting, solvent treatment, etc. These surface treatment methods are appropriately selected depending on the type of plastic film.

[0036] Examples of the functions of the functional layer include hard coat properties, anti-glare properties, fingerprint resistance, slipperiness, antistatic properties, improved writing feel, anti-Newton ring properties, and high transparency. The functional layer may have a plurality of these functions. In addition, the functions may be different depending on whether the shatterproof adhesive sheet 1 is provided on the front side of the protective panel or on the back side.

[0037] The functional layer is preferably a hard coat layer from the viewpoint of improving shatterproofness, and may be a hard coat layer having functions other than hard coat properties. For example, when the shatterproof adhesive sheet 1 is provided on the front side of the protective panel, it is preferable that the hard coat layer has fingerprint resistance, anti-glare properties, writing feel improvement, easy slip, high transparency, antistatic properties, etc. Also, when the shatterproof adhesive sheet 1 is provided on the back side of the protective panel, it is preferable that the hard coat layer has anti-Newton ring properties, anti-glare properties, high transparency, antistatic properties, etc.

[0038] In this embodiment, it is preferable that the substrate 11 does not have an anti-reflection layer. If an anti-reflection layer is provided, the hardness of the surface may decrease, and the desired harmony in appearance may not be obtained.

[0039] The hard coat layer is generally made of a cured coating composition that contains an active energy ray curable compound as an essential component and, if desired, a leveling agent, a filler, a photopolymerization initiator, etc. As the active energy ray curable compound, a multifunctional (meth)acrylate is preferably used. In this specification, the term "(meth)acrylate" refers to both acrylate and methacrylate. The same applies to other similar terms.

[0040] From the viewpoint of improving shatterproofness, the thickness of the hard coat layer is preferably from 0.5 to 20 μm, particularly preferably from 1 to 10 μm, and further preferably from 1.5 to 5 μm.

[0041] The thickness of the substrate 11 (including a functional layer, if any) is preferably 10 μm or more, more preferably 20 μm or more, particularly preferably 40 μm or more, further preferably 80 μm or more, and most preferably 105 μm or more, from the viewpoints of shatterproofness and suppression of dents. On the other hand, from the viewpoints of processability in roll-to-roll and the like, thinning of the display body, etc., the thickness is preferably 200 μm or less, particularly preferably 150 μm or less, and further preferably 130 μm or less.

[0042] The tensile modulus of the substrate 11 (including the functional layer if the substrate has a functional layer) is preferably 1.5 GPa or more, more preferably 3.0 GPa or more, and even more preferably 4.0 GPa or more, from the viewpoint of shatterproofness and suppression of dents. On the other hand, the tensile modulus is preferably 6.5 GPa or less, more preferably 6.0 GPa or less, from the viewpoint of substrate shrinkage.

[0043] 1-2. Colored adhesive layer The type of adhesive constituting the colored adhesive layer 12 of the shatterproof adhesive sheet 1 according to this embodiment is not particularly limited, and may be, for example, any of acrylic adhesives, polyester adhesives, polyurethane adhesives, rubber adhesives, silicone adhesives, etc. The adhesive may be any of emulsion type, solvent type, or solventless type, and may be any of crosslinked type or non-crosslinked type. Among them, acrylic adhesives, polyurethane adhesives, and silicone adhesives, which are excellent in adhesive properties and optical properties, are preferred, and acrylic adhesives are particularly preferred.

[0044] (a) Acrylic adhesive The acrylic adhesive may be either active energy ray curable or non-active energy ray curable. The acrylic adhesive is preferably a crosslinked type, more preferably a thermally crosslinked type.

[0045] Specifically, the acrylic adhesive in this embodiment is preferably obtained by crosslinking an adhesive composition (hereinafter sometimes referred to as "adhesive composition P") containing a (meth)acrylic acid ester polymer (A), a crosslinking agent (B), and a colorant (C). In addition, when the adhesive is an active energy ray-curable adhesive, it is preferable that the adhesive composition P further contains an active energy ray-curable component (D).

[0046] The adhesive obtained from such adhesive composition P can exhibit excellent optical properties, adhesive strength, shatterproof property, etc. In this specification, (meth)acrylic acid means both acrylic acid and methacrylic acid. The same applies to other similar terms. In addition, "polymer" includes the concept of "copolymer".

[0047] (1) Components of the adhesive composition (1-1) (Meth)acrylic acid ester polymer (A) In the present embodiment, the (meth)acrylic acid ester polymer (A) preferably contains, as a monomer unit constituting the polymer, a reactive group-containing monomer having in the molecule a reactive group that reacts with the crosslinking agent (B). The reactive group derived from the reactive group-containing monomer reacts with the crosslinking agent (B) to form a crosslinked structure (three-dimensional network structure), thereby obtaining a pressure-sensitive adhesive having the desired cohesive strength.

[0048] The reactive group-containing monomer preferably includes a monomer having a hydroxyl group in the molecule (hydroxyl group-containing monomer), a monomer having a carboxyl group in the molecule (carboxyl group-containing monomer), a monomer having an amino group in the molecule (amino group-containing monomer), etc. Among these, a hydroxyl group-containing monomer or a carboxyl group-containing monomer having excellent reactivity with the crosslinking agent (B) is preferred, and a hydroxyl group-containing monomer and a carboxyl group-containing monomer may be used in combination.

[0049] Examples of the hydroxyl group-containing monomer include (meth)acrylic acid hydroxyalkyl esters such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. Among them, from the viewpoint of the reactivity of the hydroxyl group in the obtained (meth)acrylic acid ester polymer (A) with the crosslinking agent (B) and copolymerizability with other monomers, as well as the viewpoint of good dispersibility with the colorant (C), a (meth)acrylic acid hydroxyalkyl ester having a hydroxyalkyl group having 1 to 4 carbon atoms is preferred. Specifically, for example, 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and the like are preferred, and in particular, 2-hydroxyethyl acrylate or 4-hydroxybutyl acrylate are preferred. These may be used alone or in combination of two or more.

[0050] Examples of the carboxyl group-containing monomer include ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, itaconic acid, and citraconic acid. Among them, acrylic acid is preferred in terms of the reactivity of the carboxyl group in the resulting (meth)acrylic acid ester polymer (A) with the crosslinking agent (B) and copolymerizability with other monomers. These may be used alone or in combination of two or more.

[0051] Examples of the amino group-containing monomer include aminoethyl (meth)acrylate, n-butylaminoethyl (meth)acrylate, etc. These may be used alone or in combination of two or more.

[0052] The (meth)acrylic acid ester polymer (A) preferably contains reactive group-containing monomer as a monomer unit constituting the polymer in an amount of 1% by mass or more as a lower limit, particularly preferably 3% by mass or more, and more preferably 10% by mass or more. When the reactive group-containing monomer is a hydroxyl group-containing monomer, it is preferable to contain 15% by mass or more, and particularly preferably 20% by mass or more. The (meth)acrylic acid ester polymer (A) preferably contains reactive group-containing monomer as a monomer unit constituting the polymer in an amount of 35% by mass or less as an upper limit, particularly preferably 30% by mass or less, and more preferably 25% by mass or less. When the (meth)acrylic acid ester polymer (A) contains reactive group-containing monomer as a monomer unit in the above amount, a good crosslinked structure is formed in the obtained adhesive, and desired cohesive force and adhesiveness are obtained. As a result, the obtained adhesive can, for example, prevent the protective panel from cracking by absorbing the impact even when an impact is applied, and can suppress the scattering of the fragments even if the protective panel is cracked, due to the predetermined adhesiveness. In addition, since the adhesive has excellent adhesion to the substrate constituting the shatterproof adhesive sheet, even if the fragments penetrate the adhesive layer and reach the substrate side, the shatterproof adhesive sheet itself can be prevented from being torn. In addition, the dispersibility of the colorant (C) in the adhesive tends to be good, and the adhesive obtained has good reproducibility and uniformity of the optical properties described above, and can provide better design and visibility.

[0053] It is also preferable that the (meth)acrylic acid ester polymer (A) does not contain a carboxyl group-containing monomer as a monomer unit constituting the polymer. Since a carboxyl group is an acid component, by not containing a carboxyl group-containing monomer, even if the target to which the pressure-sensitive adhesive is applied has a material that is defective due to acid, such as a transparent conductive film or a metal film, such as tin-doped indium oxide (ITO), the defects (corrosion, resistance value change, etc.) caused by acid can be suppressed. However, it is acceptable to contain a predetermined amount of a carboxyl group-containing monomer to the extent that such defects do not occur. Specifically, it is acceptable to contain a carboxyl group-containing monomer as a monomer unit in the (meth)acrylic acid ester polymer (A) in an amount of 0.1 mass% or less, preferably 0.01 mass% or less, and more preferably 0.001 mass% or less.

[0054] The (meth)acrylic acid ester polymer (A) preferably contains a (meth)acrylic acid alkyl ester as a monomer unit constituting the polymer. This allows the polymer to exhibit good adhesion. The alkyl group may be linear or branched.

[0055] From the viewpoint of adhesion, the (meth)acrylic acid alkyl ester is preferably a (meth)acrylic acid alkyl ester having an alkyl group with a carbon number of 1 to 20. Examples of the (meth)acrylic acid alkyl ester having an alkyl group with a carbon number of 1 to 20 include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, and stearyl (meth)acrylate. Among these, from the viewpoint of further improving adhesion, (meth)acrylic acid esters having an alkyl group carbon number of 1 to 8 are preferred, methyl (meth)acrylate, n-butyl (meth)acrylate, or 2-ethylhexyl (meth)acrylate are particularly preferred, and methyl acrylate, methyl methacrylate, n-butyl acrylate, or 2-ethylhexyl acrylate are even more preferred. These may be used alone or in combination of two or more.

[0056] The (meth)acrylic acid ester polymer (A) preferably contains 45% by mass or more of (meth)acrylic acid alkyl ester as a monomer unit constituting the polymer, particularly preferably 55% by mass or more, and more preferably 65% ​​by mass or more. When the lower limit of the (meth)acrylic acid alkyl ester content is as above, the (meth)acrylic acid ester polymer (A) can exhibit suitable adhesion. In addition, the dispersibility of the colorant (C) in the adhesive tends to be good, and the (meth)acrylic acid ester polymer (A) does not lose the desired adhesion. As a result, the adhesive obtained can exhibit suitable adhesion, and the reproducibility and uniformity of the optical properties described above are good, and it is possible to impart better design and visibility.

[0057] On the other hand, the (meth)acrylic acid ester polymer (A) preferably contains 99% by mass or less of (meth)acrylic acid alkyl ester as a monomer unit constituting the polymer, particularly preferably contains 95% by mass or less, and further preferably contains 90% by mass or less. Furthermore, when a hydroxyl group-containing monomer is included as a monomer constituting the polymer, it is more preferable that the (meth)acrylic acid alkyl ester is contained as a monomer unit constituting the polymer in an amount of 85% by mass or less, and particularly preferably contains 80% by mass or less. When the upper limit of the content of the (meth)acrylic acid alkyl ester is as above, other monomer components such as reactive functional group-containing monomers can be introduced into the (meth)acrylic acid ester polymer (A) in suitable amounts.

[0058] The (meth)acrylic acid ester polymer (A) preferably contains a monomer having an alicyclic structure in the molecule (an alicyclic structure-containing monomer) as a monomer unit constituting the polymer. The alicyclic structure-containing monomer is bulky, so it is presumed that the presence of the monomer in the polymer increases the distance between the polymers, and the resulting adhesive can be made excellent in flexibility. This makes the adhesive itself excellent in shatterproof property.

[0059] The carbon ring of the alicyclic structure in the alicyclic structure-containing monomer may be a saturated structure or may have an unsaturated bond in a part thereof. The alicyclic structure may be a monocyclic alicyclic structure or a polycyclic alicyclic structure such as a bicyclic or tricyclic structure. From the viewpoint of making the distance between the obtained (meth)acrylic acid ester polymer (A) appropriate and imparting a higher stress relaxation property to the adhesive, the alicyclic structure is preferably a polycyclic alicyclic structure (polycyclic structure). Furthermore, in consideration of the compatibility of the (meth)acrylic acid ester polymer (A) with other components, the polycyclic structure is particularly preferably a bicyclic to tetracyclic structure. Also, from the viewpoint of imparting stress relaxation property as described above, the carbon number of the alicyclic structure (meaning the total carbon number of the portion forming the ring, and when a plurality of rings exist independently, means the total carbon number) is usually preferably 5 or more, and particularly preferably 7 or more. On the other hand, the upper limit of the carbon number of the alicyclic structure is not particularly limited, but from the viewpoint of compatibility as described above, it is preferably 15 or less, and particularly preferably 10 or less.

[0060] Specific examples of the alicyclic structure-containing monomer include cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, adamantyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, and the like. Among these, dicyclopentanyl (meth)acrylate (alicyclic structure carbon number: 10), adamantyl (meth)acrylate (alicyclic structure carbon number: 10) or isobornyl (meth)acrylate (alicyclic structure carbon number: 7) are preferred, and isobornyl (meth)acrylate is particularly preferred, and isobornyl acrylate is even more preferred. These may be used alone or in combination of two or more.

[0061] When the (meth)acrylic acid ester polymer (A) contains an alicyclic structure-containing monomer as a monomer unit constituting the polymer, it is preferable that the alicyclic structure-containing monomer is contained in an amount of 1% by mass or more, particularly preferably 4% by mass or more, and more preferably 8% by mass or more. In addition, the (meth)acrylic acid ester polymer (A) preferably contains an alicyclic structure-containing monomer as a monomer unit constituting the polymer in an amount of 30% by mass or less, particularly preferably 22% by mass or less, and more preferably 14% by mass or less. When the content of the alicyclic structure-containing monomer is within the above range, the obtained pressure-sensitive adhesive has better shatterproofness and better adhesion to plastics.

[0062] In addition, the (meth)acrylic acid ester polymer (A) preferably contains a nitrogen atom-containing monomer as a monomer unit constituting the polymer. By making the nitrogen atom-containing monomer exist as a constituent unit in the polymer, a predetermined polarity is imparted to the adhesive, and the adhesive can have excellent affinity even for an adherend having a certain degree of polarity such as glass. As the nitrogen atom-containing monomer, a monomer having a nitrogen-containing heterocycle is preferable from the viewpoint of imparting an appropriate rigidity to the (meth)acrylic acid ester polymer (A). In addition, from the viewpoint of increasing the degree of freedom of the portion derived from the nitrogen atom-containing monomer in the higher-order structure of the adhesive that is constituted, the nitrogen atom-containing monomer preferably does not contain a reactive unsaturated double bond group other than one polymerizable group used in polymerization to form the (meth)acrylic acid ester polymer (A).

[0063] Examples of monomers having nitrogen-containing heterocycles include N-(meth)acryloylmorpholine, N-vinyl-2-pyrrolidone, N-(meth)acryloylpyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-(meth)acryloylaziridine, aziridinylethyl (meth)acrylate, 2-vinylpyridine, 4-vinylpyridine, 2-vinylpyrazine, 1-vinylimidazole, N-vinylcarbazole, and N-vinylphthalimide. Among these, N-(meth)acryloylmorpholine, which exhibits superior adhesion, is preferred, and N-acryloylmorpholine is particularly preferred. These may be used alone or in combination of two or more.

[0064] When the (meth)acrylic acid ester polymer (A) contains a nitrogen atom-containing monomer as a monomer unit constituting the polymer, it is preferable that the nitrogen atom-containing monomer is contained in an amount of 1% by mass or more, particularly preferably 4% by mass or more, and more preferably 8% by mass or more. In addition, the (meth)acrylic acid ester polymer (A) preferably contains the nitrogen atom-containing monomer as a monomer unit constituting the polymer in an amount of 20% by mass or less, particularly preferably 16% by mass or less, and more preferably 12% by mass or less. When the content of the nitrogen atom-containing monomer is within the above range, the obtained pressure-sensitive adhesive has better shatterproofness and can fully exhibit excellent adhesive strength to glass.

[0065] The (meth)acrylic acid ester polymer (A) may contain other monomers as monomer units constituting the polymer, if desired. As the other monomers, monomers not containing reactive functional groups are preferred so as not to inhibit the above-mentioned action of the reactive functional group-containing monomer. Examples of such monomers include (meth)acrylic acid alkoxyalkyl esters such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate, vinyl acetate, and styrene. These may be used alone or in combination of two or more.

[0066] The (meth)acrylic acid ester polymer (A) is preferably a linear polymer. By using a linear polymer, entanglement of molecular chains is easily caused, and an improvement in cohesive strength can be expected, so that a pressure-sensitive adhesive having excellent shatterproof properties can be easily obtained.

[0067] In addition, the (meth)acrylic acid ester polymer (A) is preferably a solution polymer obtained by a solution polymerization method. By using a solution polymer, a high molecular weight polymer can be easily obtained, and an improvement in cohesive strength can be expected, so that a pressure-sensitive adhesive with excellent shatterproof properties can be easily obtained.

[0068] The polymerization mode of the (meth)acrylic acid ester polymer (A) may be a random copolymer or a block copolymer.

[0069] The weight average molecular weight of the (meth)acrylic acid ester polymer (A) is preferably 200,000 or more as a lower limit, more preferably 300,000 or more, particularly preferably 400,000 or more, and from the viewpoint of dispersibility of the colorant (C), is even more preferably 450,000 or more. When the lower limit of the weight average molecular weight of the (meth)acrylic acid ester polymer (A) is as above, the obtained pressure-sensitive adhesive has better shatterproof properties. In addition, there is a tendency to improve the dispersibility of the colorant (C) in the pressure-sensitive adhesive, and therefore the obtained pressure-sensitive adhesive has good reproducibility and uniformity of the optical properties described above, and can be imparted with better design and visibility.

[0070] The upper limit of the weight average molecular weight of the (meth)acrylic acid ester polymer (A) is preferably 2 million or less, more preferably 1.5 million or less, and even more preferably 1 million or less. When the upper limit of the weight average molecular weight of the (meth)acrylic acid ester polymer (A) is as above, the resulting pressure-sensitive adhesive has better shatterproof properties. The weight average molecular weight in this specification is a value measured by gel permeation chromatography (GPC) in terms of standard polystyrene.

[0071] In the pressure-sensitive adhesive composition P, the (meth)acrylic acid ester polymer (A) may be used alone or in combination of two or more kinds.

[0072] (1-2) Crosslinking agent (B) The crosslinking agent (B) crosslinks the (meth)acrylic acid ester polymer (A) by heating the pressure-sensitive adhesive composition P, and can satisfactorily form a three-dimensional network structure. This improves the cohesive strength of the resulting pressure-sensitive adhesive, and provides excellent shatterproof properties.

[0073] The crosslinking agent (B) may be any that reacts with the reactive group of the (meth)acrylic acid ester polymer (A), and examples thereof include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, amine-based crosslinking agents, melamine-based crosslinking agents, aziridine-based crosslinking agents, hydrazine-based crosslinking agents, aldehyde-based crosslinking agents, oxazoline-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, and ammonium salt-based crosslinking agents. Among the above, when the reactive group of the (meth)acrylic acid ester polymer (A) is a hydroxyl group, it is preferable to use an isocyanate-based crosslinking agent that has excellent reactivity with the hydroxyl group, and when the reactive group of the (meth)acrylic acid ester polymer (A) is a carboxyl group, it is preferable to use an epoxy-based crosslinking agent that has excellent reactivity with the carboxyl group. The crosslinking agent (B) may be used alone or in combination of two or more.

[0074] The isocyanate-based crosslinking agent contains at least a polyisocyanate compound. Examples of the polyisocyanate compound include aromatic polyisocyanates such as tolylene diisocyanate, diphenylmethane diisocyanate, and xylylene diisocyanate, aliphatic polyisocyanates such as hexamethylene diisocyanate, alicyclic polyisocyanates such as isophorone diisocyanate and hydrogenated diphenylmethane diisocyanate, and their biuret and isocyanurate forms, as well as adducts which are reactants with low-molecular active hydrogen-containing compounds such as ethylene glycol, propylene glycol, neopentyl glycol, trimethylolpropane, and castor oil. Among these, trimethylolpropane-modified aromatic polyisocyanates, particularly trimethylolpropane-modified tolylene diisocyanate or trimethylolpropane-modified xylylene diisocyanate, are preferred from the viewpoint of reactivity with hydroxyl groups.

[0075] Examples of epoxy crosslinking agents include 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, N,N,N',N'-tetraglycidyl-m-xylylenediamine, ethylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane diglycidyl ether, diglycidylaniline, diglycidylamine, etc. Among these, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane is preferred from the viewpoint of reactivity with a carboxy group.

[0076] The content of the crosslinking agent (B) in the adhesive composition P is preferably 0.01 parts by mass or more, more preferably 0.03 parts by mass or more, and even more preferably 0.05 parts by mass or more, based on 100 parts by mass of the (meth)acrylic acid ester polymer (A). The content is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, more preferably 1 part by mass or less, and even more preferably 0.4 parts by mass or less. When the content of the crosslinking agent (B) is within the above range, the resulting adhesive exhibits good cohesive force and has excellent shatterproof properties.

[0077] (1-3) Colorant (C) The colorant (C) may be a pigment or a dye. The pigment may be an inorganic pigment or an organic pigment. From the viewpoint of the durability of the resulting adhesive, inorganic pigments are preferred. The color of the colorant can be appropriately selected in consideration of the design of the display, particularly the harmony of the appearance, and is generally preferably a dark or deep color such as black, brown, navy blue, purple, or blue, and particularly preferably black.

[0078] Examples of inorganic pigments include carbon black, cobalt-based pigments, iron-based pigments, chromium-based pigments, titanium-based pigments, vanadium-based pigments, zirconium-based pigments, molybdenum-based pigments, ruthenium-based pigments, platinum-based pigments, ITO (indium tin oxide)-based pigments, and ATO (antimony tin oxide)-based pigments.

[0079] Examples of organic pigments and organic dyes include aminium-based dyes, cyanine-based dyes, merocyanine-based dyes, croconium-based dyes, squalium-based dyes, azulenium-based dyes, polymethine-based dyes, naphthoquinone-based dyes, pyrylium-based dyes, phthalocyanine-based dyes, naphthalocyanine-based dyes, naphtholactam-based dyes, azo-based dyes, condensed azo-based dyes, indigo-based dyes, perinone-based dyes, perylene-based dyes, dioxazine-based dyes, quinacridone-based dyes, isoindolinone-based dyes, quinophthalone-based dyes, pyrrole-based dyes, thioindigo-based dyes, metal complex-based dyes (metal complex dyes), dithiol metal complex-based dyes, indolephenol-based dyes, triarylmethane-based dyes, anthraquinone-based dyes, dioxazine-based dyes, naphthol-based dyes, azomethine-based dyes, benzimidazolone-based dyes, pyranthrone-based dyes, and threne-based colors.

[0080] Examples of black pigments include carbon black, copper oxide, iron oxide, manganese dioxide, aniline black, activated carbon, etc. Examples of black dyes include high-concentration vegetable dyes and azo dyes.

[0081] The above pigments or dyes can be used in appropriate mixtures depending on the purpose.

[0082] From the viewpoint of the above-mentioned lightness L* (and chromaticity a* and chromaticity b*), carbon black, nigrosine-based black dyes, and chromate-based black dyes are preferred among the above colorants. Note that the carbon black may or may not have been subjected to a predetermined treatment (for example, a solvent-philic treatment) on its surface.

[0083] The colorant is preferably one in which the lower limit of the average haze, which is the average value of the haze value at a wavelength of 780 nm and the haze value at a wavelength of 380 nm when the colorant is diluted 10,000 times with ethyl acetate, is 1% or more, particularly preferably 2% or more, and more preferably 3% or more. The colorant is preferably one in which the upper limit of the average haze is 60% or less, preferably 40% or less, particularly preferably 30% or less, more preferably 20% or less, and most preferably 10% or less. By using an appropriate amount of such a colorant, the obtained adhesive has good reproducibility and uniformity of the optical properties described above.

[0084] Moreover, the colorant is preferably one in which the difference between the haze value at a wavelength of 780 nm and the haze value at a wavelength of 380 nm of a solution obtained by diluting the colorant 10,000 times with ethyl acetate is 30 points or less, more preferably 25 points or less, particularly preferably 20 points or less, further preferably 16 points or less, and most preferably 10 points or less. By using an appropriate amount of such a colorant, the obtained adhesive has good reproducibility and uniformity of the optical properties described above.

[0085] The lower limit of the difference in haze values ​​may be 0 points, but from the viewpoint of making it easier to adjust the optical properties of the pressure-sensitive adhesive layer 11 described above to be suitable, it is preferably 0.1 points or more, more preferably 0.5 points or more, particularly preferably 1 point or more, and even more preferably 3 points or more.

[0086] The haze value at a wavelength of 780 nm of a solution obtained by diluting the above-mentioned colorant 10,000 times with ethyl acetate is preferably 0.1 to 50%, more preferably 0.5 to 40%, particularly preferably 1 to 30%, even more preferably 1.5 to 20%, and most preferably 2 to 10%. The haze value at a wavelength of 380 nm of a solution obtained by diluting the above-mentioned colorant 10,000 times with ethyl acetate is preferably 1 to 60%, more preferably 3 to 50%, particularly preferably 6 to 40%, even more preferably 8 to 30%, and most preferably 10 to 20%. This makes it easier to meet the above-mentioned difference in haze value.

[0087] Furthermore, the standard deviation of the haze value at each wavelength in the wavelength range of 380 nm to 780 nm (i.e., 380 nm, 385 nm, 390 nm, . . . , 775 nm, 780 nm) at 5 nm intervals in a solution obtained by diluting the above colorant 10,000 times with ethyl acetate is preferably 10 or less, more preferably 8 or less, particularly preferably 5 or less, and even more preferably 2 or less. The lower limit of the above standard deviation is most preferably 0, but is usually preferably 0.1 or more, particularly preferably 0.5 or more, and even more preferably 1 or more. This allows the obtained adhesive to have good reproducibility and uniformity of the optical properties described above.

[0088] In the colored adhesive layer 12, the content of the colorant (C) relative to 100 parts by mass of the (meth)acrylic acid ester polymer (A) is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, particularly preferably 0.1 parts by mass or more, and even more preferably 0.3 parts by mass or more. The content is preferably 2 parts by mass or less, more preferably 1.5 parts by mass or less, particularly preferably 1.2 parts by mass or less, even more preferably 0.9 parts by mass or less, and most preferably 0.6 parts by mass or less. By having the content of the colorant (C) in the above range, the above-mentioned optical characteristics are easily satisfied, and the appearance harmony and visibility of the display body are easily improved.

[0089] (1-4) Active energy ray-curable component (D) In the adhesive obtained by crosslinking the adhesive composition P and curing it with active energy rays, it is presumed that the active energy ray curable components (D) polymerize with each other, and the polymerized active energy ray curable components (D) become entangled with the crosslinked structure (three-dimensional network structure) of the (meth)acrylic acid ester polymer (A). An adhesive having such a high-order structure exhibits excellent shatterproof properties and is particularly excellent in durability.

[0090] The active energy ray curable component (D) is not particularly limited as long as it is a component that is cured by irradiation with active energy rays and can obtain the above-mentioned effects, and may be any of a monomer, an oligomer, or a polymer, or a mixture thereof. Among them, a polyfunctional acrylate monomer having excellent durability can be preferably mentioned.

[0091] Examples of polyfunctional acrylate monomers include 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, neopentyl glycol adipate di(meth)acrylate, hydroxypivalic acid neopentyl glycol di(meth)acrylate, dicyclopentanyl di(meth)acrylate, tricyclodecane dimethanol (meth)acrylate, caprolactone-modified dicyclopentenyl di(meth)acrylate, ethylene oxide-modified phosphoric acid di(meth)acrylate, di(acryloxyethyl)isocyanurate, allylated cyclohexyl di(meth)acrylate, ethoxylated bisphenol A diacrylate, 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene Examples of the acrylate include bifunctional acrylates such as trimethylolpropane tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, propionic acid modified dipentaerythritol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, propylene oxide modified trimethylolpropane tri(meth)acrylate, tris(acryloxyethyl)isocyanurate, ε-caprolactone modified tris-(2-(meth)acryloxyethyl)isocyanurate, tetrafunctional acrylates such as diglycerin tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentafunctional acrylates such as propionic acid modified dipentaerythritol penta(meth)acrylate, and hexafunctional acrylates such as dipentaerythritol hexa(meth)acrylate, caprolactone modified dipentaerythritol hexa(meth)acrylate. These may be used alone or in combination of two or more. From the viewpoints of compatibility with the (meth)acrylic acid ester polymer (A) and dispersibility of the colorant (C), the polyfunctional acrylate monomer preferably has a molecular weight of less than 1,000.

[0092] Among the above, from the viewpoint of durability of the obtained pressure-sensitive adhesive, polyfunctional acrylate monomers containing an isocyanurate structure in the molecule, such as di(acryloxyethyl)isocyanurate, tris(acryloxyethyl)isocyanurate, and ε-caprolactone-modified tris-(2-(meth)acryloxyethyl)isocyanurate, or polyfunctional acrylate monomers containing a cyclic structure (particularly a cycloalkane structure) in the molecule, such as tricyclodecane dimethanol (meth)acrylate, are preferred, as are polyfunctional acrylates having three or more functionalities and containing an isocyanurate structure in the molecule. More preferred are ε-caprolactone-modified tris-(2-(meth)acryloxyethyl)isocyanurate or tricyclodecane dimethanol (meth)acrylate, more preferred are ε-caprolactone-modified tris-(2-acryloxyethyl)isocyanurate or tricyclodecane dimethanol acrylate, and most preferred are ε-caprolactone-modified tris-(2-acryloxyethyl)isocyanurate or tricyclodecane dimethanol acrylate.

[0093] The content of the active energy ray-curable component (D) in the adhesive composition P is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 4 parts by mass or more, relative to 100 parts by mass of the (meth)acrylic acid ester polymer (A), from the viewpoint of improving the durability of the adhesive after curing with active energy rays. On the other hand, the content is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 6 parts by mass or less, from the viewpoint of the adhesive strength of the adhesive after curing with active energy rays.

[0094] (1-5) Photopolymerization initiator (E) When ultraviolet rays are used as the active energy rays for curing the adhesive composition P, it is preferable that the adhesive composition P further contains a photopolymerization initiator (E). By containing the photopolymerization initiator (E) in this manner, the active energy ray curable component (D) can be polymerized efficiently, and the polymerization curing time and the irradiation dose of the active energy rays can be reduced.

[0095] Examples of such photopolymerization initiators (E) include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin-n-butyl ether, benzoin isobutyl ether, acetophenone, dimethylaminoacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholino-propan-1-one, 4-(2-hydroxyethoxy)phenyl-2-(hydroxy-2-propyl)ketone, benzophenone, p-phenylbenzophenone, Examples of the benzoxanthone include 4,4'-diethylaminobenzophenone, dichlorobenzophenone, 2-methylanthraquinone, 2-ethylanthraquinone, 2-tertiary-butylanthraquinone, 2-aminoanthraquinone, 2-methylthioxanthone, 2-ethylthioxanthone, 2-chlorothioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, benzyl dimethyl ketal, acetophenone dimethyl ketal, p-dimethylaminobenzoic acid ester, oligo[2-hydroxy-2-methyl-1[4-(1-methylvinyl)phenyl]propanone], 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide. These may be used alone or in combination of two or more.

[0096] Among the above, phosphine oxide-based photopolymerization initiators are preferred because they are easily cleaved and can reliably cure the adhesive even when irradiated with ultraviolet light through a member containing an ultraviolet absorber or when the adhesive contains an ultraviolet absorber. Specifically, 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, etc. are preferred.

[0097] The content of the photopolymerization initiator (E) in the adhesive composition P is preferably 0.1 parts by mass or more as a lower limit, more preferably 1 part by mass or more, and even more preferably 5 parts by mass or more, based on 100 parts by mass of the active energy ray-curable component (D).The content of the photopolymerization initiator (E) in the adhesive composition P is preferably 30 parts by mass or less as an upper limit, more preferably 20 parts by mass or less, and even more preferably 12 parts by mass or less.

[0098] (1-6) Various additives If desired, various additives that are commonly used in acrylic adhesives, such as a silane coupling agent, an ultraviolet absorber, an antirust agent, an antistatic agent, a tackifier, an antioxidant, a light stabilizer, a softener, a refractive index adjuster, etc., can be added to the adhesive composition P. Note that polymerization solvents and dilution solvents described below are not included in the additives that constitute the adhesive composition P.

[0099] Among the above, the adhesive composition P preferably contains a silane coupling agent, which improves adhesion to the adherend, whether the adherend is a plastic plate or a glass member, and provides better shatterproof properties.

[0100] The silane coupling agent is preferably an organosilicon compound having at least one alkoxysilyl group in the molecule, which has good compatibility with the (meth)acrylic acid ester polymer (A) and has optical transparency.

[0101] Examples of such silane coupling agents include polymerizable unsaturated group-containing silicon compounds such as vinyltrimethoxysilane, vinyltriethoxysilane, and methacryloxypropyltrimethoxysilane; epoxy structure-containing silicon compounds such as 3-glycidoxypropyltrimethoxysilane and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; mercapto group-containing silicon compounds such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, and 3-mercaptopropyldimethoxymethylsilane. , 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, and other amino group-containing silicon compounds, 3-chloropropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, and condensates of at least one of these with alkyl group-containing silicon compounds such as methyltriethoxysilane, ethyltriethoxysilane, methyltrimethoxysilane, and ethyltrimethoxysilane. These may be used alone or in combination of two or more.

[0102] The content of the silane coupling agent in the adhesive composition P is preferably 0.01 parts by mass or more, particularly preferably 0.05 parts by mass or more, and even more preferably 0.1 parts by mass or more, relative to 100 parts by mass of the (meth)acrylic acid ester polymer (A). The content is also preferably 1 part by mass or less, particularly preferably 0.5 parts by mass or less, and even more preferably 0.3 parts by mass or less. By including the silane coupling agent in the above amount, the adhesion of the shatterproof adhesive sheet using the obtained adhesive to the adherend is improved, and more excellent shatterproofness can be exhibited.

[0103] It is also preferable that the adhesive composition P contains an ultraviolet absorbing agent. Examples of ultraviolet absorbing agents include compounds such as benzophenones, benzotriazoles, benzoates, benzoxazinones, triazines, phenyl salicylates, cyanoacrylates, and nickel complex salts. Among them, from the viewpoint of compatibility with the (meth)acrylic acid ester polymer (A) and dispersibility with the colorant (C), benzophenones, benzotriazoles, and triazines are preferred, and benzophenones are particularly preferred. These may be used alone or in combination of two or more.

[0104] When the adhesive composition P contains an ultraviolet absorber, the content of the ultraviolet absorber is preferably 0.01 parts by mass or more, particularly preferably 0.05 parts by mass or more, and even more preferably 0.1 parts by mass or more, relative to 100 parts by mass of the (meth)acrylic acid ester polymer (A). The content is preferably 1 part by mass or less, particularly preferably 0.5 parts by mass or less, and even more preferably 0.2 parts by mass or less. By containing the ultraviolet absorber in the above amount, even if there is a member inside the display body that is prone to ultraviolet degradation, the shatterproof adhesive sheet exhibits an ultraviolet shielding effect, and the deterioration of the member due to ultraviolet rays can be prevented.

[0105] (2) Preparation of adhesive composition The adhesive composition P can be produced by producing a (meth)acrylic acid ester polymer (A), mixing the obtained (meth)acrylic acid ester polymer (A) with a crosslinking agent (B) and a colorant (C), and, if desired, adding an active energy ray-curable component (D), a photopolymerization initiator (E), additives, etc.

[0106] The (meth)acrylic acid ester polymer (A) can be produced by polymerizing a mixture of monomers constituting the polymer by a normal radical polymerization method. The polymerization of the (meth)acrylic acid ester polymer (A) is preferably carried out by a solution polymerization method using a polymerization initiator as desired. However, the present invention is not limited thereto, and the polymerization may be carried out without a solvent. Examples of the polymerization solvent include ethyl acetate, n-butyl acetate, isobutyl acetate, toluene, acetone, hexane, methyl ethyl ketone, etc., and two or more of them may be used in combination.

[0107] Examples of the polymerization initiator include azo compounds and organic peroxides, and two or more of them may be used in combination. Examples of the azo compounds include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane 1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), dimethyl 2,2'-azobis(2-methylpropionate), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), and 2,2'-azobis[2-(2-imidazolin-2-yl)propane].

[0108] Examples of organic peroxides include benzoyl peroxide, t-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl)peroxydicarbonate, t-butyl peroxyneodecanoate, t-butyl peroxypivalate, (3,5,5-trimethylhexanoyl)peroxide, dipropionyl peroxide, and diacetyl peroxide.

[0109] In the above polymerization step, the weight average molecular weight of the resulting polymer can be adjusted by adding a chain transfer agent such as 2-mercaptoethanol.

[0110] After the (meth)acrylic acid ester polymer (A) is obtained, the crosslinking agent (B), the colorant (C), and optionally the dilution solvent, the active energy ray curable component (D), the photopolymerization initiator (E), the additives, etc. are added to the solution of the (meth)acrylic acid ester polymer (A) and thoroughly mixed to obtain a solvent-diluted adhesive composition P (coating solution). When any of the above components is in a solid state or when precipitation occurs when mixed with other components in an undiluted state, the component may be dissolved or diluted alone in a dilution solvent before mixing with other components.

[0111] Examples of the dilution solvent include aliphatic hydrocarbons such as hexane, heptane, and cyclohexane; aromatic hydrocarbons such as toluene and xylene; halogenated hydrocarbons such as methylene chloride and ethylene chloride; alcohols such as methanol, ethanol, propanol, butanol, and 1-methoxy-2-propanol; ketones such as acetone, methyl ethyl ketone, 2-pentanone, isophorone, and cyclohexanone; esters such as ethyl acetate and butyl acetate; and cellosolve-based solvents such as ethyl cellosolve.

[0112] The concentration and viscosity of the coating solution thus prepared are not particularly limited as long as they are within the range that allows coating, and can be appropriately selected according to the situation. For example, the adhesive composition P is diluted so that the concentration becomes 10 to 60 mass %. In addition, when obtaining the coating solution, the addition of a dilution solvent or the like is not a necessary condition, and if the adhesive composition P has a viscosity that allows coating, it is not necessary to add a dilution solvent. In this case, the adhesive composition P becomes a coating solution in which the polymerization solvent of the (meth)acrylic acid ester polymer (A) itself serves as the dilution solvent.

[0113] (3) Formation of adhesive layer The colored adhesive layer 12 in this embodiment is preferably made of an adhesive obtained by crosslinking (a coating layer of) the adhesive composition P. The crosslinking of the adhesive composition P can usually be carried out by a heat treatment. This heat treatment can also serve as a drying treatment for volatilizing a diluting solvent and the like from the coating layer of the adhesive composition P applied to a desired object.

[0114] The heating temperature in the heat treatment is preferably 50 to 150° C., and more preferably 70 to 120° C. The heating time is preferably 10 seconds to 10 minutes, and more preferably 50 seconds to 2 minutes.

[0115] After the heat treatment, a curing period of about 1 to 2 weeks may be provided at room temperature (e.g., 23°C, 50% RH) as necessary. If this curing period is required, the adhesive is formed after the curing period has elapsed, and if no curing period is required, the adhesive is formed after the heat treatment is completed.

[0116] By the above heat treatment (and curing), the (meth)acrylic acid ester polymer (A) is sufficiently crosslinked via the crosslinking agent (B).

[0117] (4) Thickness of the colored adhesive layer The thickness of the colored adhesive layer 12 has a lower limit of preferably 5 μm or more, more preferably 10 μm or more, and particularly preferably 20 μm or more. When the lower limit of the thickness of the colored adhesive layer 12 is within the above range, the above-mentioned optical properties are easily satisfied in relation to the content of the colorant (C), and the desired adhesive strength is easily exhibited.

[0118] The upper limit of the thickness of the colored adhesive layer 12 is preferably 80 μm or less, more preferably 60 μm or less, and from the viewpoint of the pencil hardness of the surface of the substrate 11 side of the shatterproof adhesive sheet 1, it is particularly preferably 40 μm or less, and even more preferably 30 μm or less. When the upper limit of the thickness of the colored adhesive layer 12 is as above, the processability is good. Also, appearance defects due to impressions and the like are unlikely to occur. Furthermore, in relation to the content of the colorant (C), the above-mentioned optical properties are easily satisfied. The colored adhesive layer 12 may be formed as a single layer, or may be formed by laminating multiple layers.

[0119] (b) Polyurethane adhesive The urethane-based pressure-sensitive adhesive in this embodiment contains a crosslinked urethane resin, and is preferably produced using a polyurethane polyol and a polyisocyanate crosslinking agent.

[0120] The polyurethane polyol is obtained by reacting a polyol with a polyisocyanate so that the equivalent ratio of isocyanate groups to hydroxyl groups is less than 1. As the polyol, polyester polyol, polyether polyol, etc. are preferable. As the polyether polyol, for example, polypropylene glycol, polyethylene glycol, polytetramethylene glycol, etc. are preferable.

[0121] The average number of functional groups per molecule of the polyether polyol is preferably 2.2 to 3.4, more preferably 2.3 to 3.3, and even more preferably 2.4 to 3.2. The number average molecular weight (Mn) of the polyether polyol is preferably 300 to 7000, and more preferably 350 to 6000.

[0122] Examples of polyisocyanates constituting polyurethane polyol include aromatic polyisocyanates, aliphatic polyisocyanates, araliphatic polyisocyanates, alicyclic polyisocyanates, etc. Also included are their trimethylolpropane adducts, biurets, nurates, etc. Examples of aromatic polyisocyanates include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, etc.

[0123] The polymerization reaction between the polyol and the polyisocyanate is generally carried out using a catalyst, such as a tin-based organometallic compound such as dioctyltin dilaurate.

[0124] On the other hand, examples of the polyisocyanate crosslinking agent include the above-mentioned trimethylolpropane adduct, biuret, and nurate of the polyisocyanate. The amount of the polyisocyanate crosslinking agent to be blended with the polyurethane polyol is preferably such that the equivalent ratio of the isocyanate group to the hydroxyl group is 0.5 or more and 1.5 or less.

[0125] The amount of colorant (C) in the urethane-based adhesive and the thickness of the colored adhesive layer 12 are the same as in the case of the acrylic-based adhesive described above.

[0126] (c) Silicone-based adhesive The silicone-based adhesive in this embodiment may be a condensation type silicone adhesive or an addition reaction type silicone adhesive, but an addition reaction type silicone adhesive is preferred. The addition reaction type silicone adhesive is preferably one that contains an addition reaction type silicone resin obtained from a first polydimethylsiloxane having at least two alkenyl groups in one molecule and a second polydimethylsiloxane having at least two hydrosilyl groups in one molecule, a silicone resin, and a catalyst.

[0127] Silicone resins include, for example, monofunctional siloxane units [(CH3)3SiO 1 / 2] and tetrafunctional siloxane units [SiO 4 / 2 and Q units.] The molar ratio of M units / Q units is preferably 0.6 to 1.7.

[0128] The amount of silicone resin per 100 parts by mass of addition reaction type silicone resin is preferably 10 to 200 parts by mass, more preferably 15 to 100 parts by mass, and even more preferably 20 to 80 parts by mass. By making the amount of silicone resin 10 parts by mass or more, it is possible to obtain a desired adhesive strength. Furthermore, by making the amount of silicone resin 200 parts by mass or less, it is possible to obtain good reworkability, and in the event of a bonding error, it is possible to reuse display body components, especially expensive display body components.

[0129] The catalyst is not particularly limited as long as it can cure the addition reaction type silicone resin (addition reaction between the first polydimethylsiloxane and the second polydimethylsiloxane), but among them, platinum group metal compounds are preferred. The amount of catalyst blended per 100 parts by mass of the addition reaction type silicone resin is preferably 0.01 to 3 parts by mass, particularly preferably 0.05 to 2 parts by mass, in terms of platinum content.

[0130] The amount of colorant (C) in the silicone-based adhesive and the thickness of the colored adhesive layer 12 are the same as in the case of the acrylic-based adhesive described above.

[0131] 1-3.Release sheet The release sheet 13 protects the colored adhesive layer 12 until the shatterproof adhesive sheet 1 is used, and is peeled off when the shatterproof adhesive sheet 1 (colored adhesive layer 12) is used. In the shatterproof adhesive sheet 1 according to this embodiment, the release sheet 13 is not necessarily required.

[0132] Examples of the release sheet 13 include polyethylene films, polypropylene films, polybutene films, polybutadiene films, polymethylpentene films, polyvinyl chloride films, vinyl chloride copolymer films, polyethylene terephthalate films, polyethylene naphthalate films, polybutylene terephthalate films, polyurethane films, ethylene vinyl acetate films, ionomer resin films, ethylene-(meth)acrylic acid copolymer films, ethylene-(meth)acrylic acid ester copolymer films, polystyrene films, polycarbonate films, polyimide films, and fluororesin films. Crosslinked films of these films are also used. Furthermore, laminated films of these films may also be used.

[0133] It is preferable that a release treatment is performed on the release surface (particularly the surface in contact with the colored adhesive layer 12) of the release sheet 13. Examples of release agents used in the release treatment include alkyd-based, silicone-based, fluorine-based, unsaturated polyester-based, polyolefin-based, and wax-based release agents.

[0134] The thickness of the release sheet 13 is not particularly limited, but is usually about 20 to 150 μm.

[0135] 2. Physical properties (1) Gel fraction The gel fraction of the adhesive constituting the colored adhesive layer 12 is preferably 30% or more as a lower limit, more preferably 40% or more, and particularly preferably 50% or more. When the lower limit of the gel fraction of the adhesive is as above, the cohesive force of the adhesive is high, and more excellent shatterproof properties can be exhibited. In addition, the gel fraction of the adhesive according to the present embodiment is preferably 95% or less as an upper limit, more preferably 90% or less, particularly preferably 85% or less, and even more preferably 80% or less. When the upper limit of the gel fraction of the adhesive is as above, the adhesive does not become too hard and exhibits good adhesive strength, and therefore more excellent shatterproof properties can be exhibited. Here, the method for measuring the gel fraction of the adhesive is as shown in the test example described later.

[0136] (2) L*a*b* of colored adhesive layer The lightness L* of the colored adhesive layer 12, as defined by the CIE1976 L*a*b* color system, is preferably 92 or less, more preferably 86 or less, particularly preferably 83 or less, and even more preferably 80 or less. This makes it easier to set the lightness L* of the shatterproof adhesive sheet 1 to the preferred value described above, and when the display is turned off, it is possible to give the display a sense of unity with the black frame material and printed layer, improving the harmony of the appearance.

[0137] On the other hand, from the viewpoint of improving the design through appearance harmony and the visibility of the display, the lower limit value of the lightness L* is preferably 10 or more, more preferably 20 or more, particularly preferably 40 or more, further preferably 50 or more, and most preferably 60 or more.

[0138] Furthermore, the chromaticity a* of the colored adhesive layer 12, as defined by the CIE1976 L*a*b* color system, is preferably -20 to 20, more preferably -10 to 10, particularly preferably -5 to 5, further preferably -2 to 2, and most preferably -1.4 to 1.4. When the chromaticity a* is within the above range, the chromaticity a* of the shatterproof adhesive sheet 1 can be easily adjusted to the preferred value described above, improving the visibility of the display and further improving the design, particularly the appearance harmony of an in-vehicle display.

[0139] Furthermore, the chromaticity b* of the colored adhesive layer 12, as defined by the CIE1976 L*a*b* color system, is preferably -20 to 20, more preferably -10 to 10, particularly preferably -5 to 5, further preferably -2 to 2, and most preferably -1 to 1. When the chromaticity b* is within the above range, the chromaticity b* of the shatterproof adhesive sheet 1 can be easily adjusted to the preferred value described above, improving the visibility of the display and further improving the design, particularly the appearance harmony of an in-vehicle display.

[0140] (3) Total light transmittance of colored adhesive layer The total light transmittance of the colored adhesive layer 12 is preferably 10% or more, more preferably 20% or more, particularly preferably 30% or more, and even more preferably 40% or more. This improves the visibility of the image / video in the obtained display. The upper limit of the total light transmittance is not particularly limited, but is usually 100% or less, and considering the relationship with the lightness L* and the improvement in blackness in the image / video of the display, it is preferably 95% or less, more preferably 85% or less, particularly preferably 75% or less, even more preferably 65% ​​or less, and most preferably 55% or less.

[0141] (4) Haze value The haze value of the shatterproof adhesive sheet 1 according to the present embodiment is usually 0% or more, preferably 0.1% or more, more preferably 1% or more, particularly preferably 3% or more, and most preferably 6% or more. The lower limit of the haze value of the colored adhesive layer 12 is as described above, so that the above-mentioned lightness L* is easily satisfied. On the other hand, the haze value of the colored adhesive layer 12 is preferably 60% or less, more preferably 40 or less, particularly preferably 25% or less, further preferably 15% or less, and most preferably 10% or less. The upper limit of the haze value of the colored adhesive layer 12 is as described above, so that the above-mentioned total image clarity value and lightness L* of the shatterproof adhesive sheet 1 are easily satisfied. The haze value in this specification is a value measured in accordance with JIS K7136:2000.

[0142] The haze value of the colored adhesive layer 12 is usually 0% or more, preferably 0.1% or more, more preferably 0.5% or more, and particularly preferably 1% or more. When the lower limit of the haze value of the colored adhesive layer 12 is as above, the above-mentioned lightness L* is easily satisfied. On the other hand, the haze value of the colored adhesive layer 12 is preferably 60% or less, more preferably 40 or less, particularly preferably 20% or less, and even more preferably 8% or less. When the upper limit of the haze value of the colored adhesive layer 12 is as above, the above-mentioned total image clarity and lightness L* of the shatterproof adhesive sheet 1 are easily satisfied.

[0143] (5) Adhesive strength The adhesive strength of the shatterproof adhesive sheet 1 according to the present embodiment to soda lime glass is preferably 0.05 N / 25 mm or more as a lower limit, more preferably 0.1 N / 25 mm or more, particularly preferably 1 N / 25 mm or more, and even more preferably 5 N / 25 mm or more. When the adhesive strength has a lower limit as above, the shatterproof property is more excellent. In addition, the adhesive strength of the shatterproof adhesive sheet 1 according to the present embodiment to soda lime glass is preferably 50 N / 25 mm or less as an upper limit, more preferably 35 N / 25 mm or less, and particularly preferably 25 N / 25 mm or less. When the adhesive strength has an upper limit as above, good reworkability is obtained, and when a bonding error occurs, it is possible to reuse the display body constituent members, especially expensive display body constituent members.

[0144] Here, the adhesive strength in this specification basically refers to the adhesive strength measured by the 180-degree peeling method according to JIS Z0237:2009, the measurement sample is 25 mm wide and 100 mm long, the measurement sample is attached to an adherend, pressurized at 0.5 MPa and 50°C for 20 minutes, and then left for 24 hours under normal pressure, 23°C, and 50% RH, and then measured at a peel speed of 300 mm / min. In the case of an active energy ray-curable adhesive, the adhesive strength is the adhesive strength of the adhesive layer cured by active energy ray after being attached to the adherend.

[0145] (6)Pencil hardness The pencil hardness of the surface on the substrate 11 side of the shatterproof adhesive sheet 1 according to this embodiment is preferably F or more, and particularly preferably H or more. When the shatterproof adhesive sheet 1 has such a pencil hardness, the surface on the substrate 11 side of the shatterproof adhesive sheet 1 has sufficient hardness. Therefore, when the shatterproof adhesive sheet 1 is used on the front side of a protective panel, it can provide excellent surface protection. In addition, when the shatterproof adhesive sheet 1 is used on the back side of a protective panel, it can provide excellent impact resistance. The method for measuring the pencil hardness in the present invention is as shown in the test example described later.

[0146] 3. Manufacturing of shatterproof adhesive sheets In one example of manufacturing the shatterproof adhesive sheet 1, a coating solution of the adhesive composition P is applied to the release surface of the release sheet 13, and a heat treatment is carried out to thermally crosslink the adhesive composition P to form a coating layer, and then the substrate 11 is laminated to the coating layer. At this time, when the substrate 11 has a functional layer on one side, the side on which the functional layer does not exist is usually brought into contact with the coating layer.

[0147] If a curing period is required, a curing period is allowed, or if no curing period is required, the coating layer is left as is to become the colored adhesive layer 12. This results in the shatterproof adhesive sheet 1. The conditions for the heat treatment and curing are as described above.

[0148] The coating solution of the pressure-sensitive adhesive composition P can be applied by, for example, bar coating, knife coating, roll coating, blade coating, die coating, gravure coating, or the like.

[0149] [Display body] The display according to one embodiment of the present invention includes a protective panel, and the above-mentioned shatterproof adhesive sheet is provided on one or both sides of the protective panel. The shatterproof adhesive sheet may be attached directly to the protective panel or may be attached via another layer.

[0150] The display body according to the present embodiment may have a frame material or the like on the periphery as an example of a peripheral member, or may have a frame-shaped printed layer or a printed layer showing characters and symbols formed on a part of one of the display body constituent members constituting the display body. Also, it may have both of them.

[0151] In the display according to the present embodiment, a shatterproof adhesive sheet having a colored adhesive layer is provided on the protective panel, so that when the display is turned off, the display has a good appearance harmony with surrounding components such as a frame material, a frame-shaped printed layer, a printed layer showing characters and symbols, etc., and thus the design is improved. Even if the protective panel is cracked due to a large impact such as a fall in a display for mobile use, or due to an accident in a display for vehicle use, the shatterproof adhesive sheet attached to the protective panel prevents the cracked protective panel from scattering.

[0152] 2 and 3 show a specific example of a display according to this embodiment. 2, the display device 10A according to the first embodiment is configured to include, from the bottom up, a display module 7, a film sensor 5 laminated thereon via an adhesive layer 6, a protective panel 2 with a patterned transparent conductive film 3 laminated thereon via an adhesive layer 4, and a shatterproof adhesive sheet 1 (with the release sheet 13 having been peeled off) attached onto the protective panel 2 via a colored adhesive layer 12. That is, in this display device 10A, the shatterproof adhesive sheet 1 is provided on the front side of the protective panel 2 (the side opposite the display module 7).

[0153] 3, the display device 10B according to the second embodiment is configured to include, from the bottom, a display module 7, a film sensor 5 laminated thereon via an adhesive layer 6, a shatterproof adhesive sheet 1 (with the release sheet 13 having been peeled off) laminated thereon via an adhesive layer 4, and a protective panel 2 with a patterned transparent conductive film 3 laminated thereon via a colored adhesive layer 12 of the shatterproof adhesive sheet 1. That is, in this display device 10B, the shatterproof adhesive sheet 1 is provided on the back side of the protective panel 2 (the display module 7 side).

[0154] In the above-described display devices 10A and 10B, the transparent conductive film 3 is provided on the protective panel 2, but the present invention is not limited to this, and the transparent conductive film 3 may be provided in another location.

[0155] Examples of the display module 7 include a liquid crystal (LCD) module, a light emitting diode (LED) module, an organic electroluminescence (organic EL) module, and electronic paper.

[0156] The adhesive layer 6 and the adhesive layer 4 may be formed of a desired adhesive or adhesive sheet, and may be formed of an adhesive similar to that of the colored adhesive layer 12 of the shatterproof adhesive sheet 1 (but preferably does not contain a colorant). Examples of the desired adhesive include acrylic adhesives, rubber adhesives, silicone adhesives, urethane adhesives, polyester adhesives, polyvinyl ether adhesives, etc., and among these, acrylic adhesives are preferred.

[0157] The film sensor 5 is usually composed of a base film 51 and a patterned transparent conductive film 52. The base film 51 is not particularly limited, but examples of the base film that can be used include a polyethylene terephthalate film, a polyethylene naphthalate film, a polycarbonate film, a polymethyl methacrylate film, a triacetyl cellulose film, and a polypropylene film.

[0158] Examples of the transparent conductive film 52 include metals such as platinum, gold, silver, and copper; oxides such as tin oxide, indium oxide, cadmium oxide, zinc oxide, and zinc dioxide; complex oxides such as tin-doped indium oxide (ITO), zinc oxide-doped indium oxide, fluorine-doped indium oxide, antimony-doped tin oxide, fluorine-doped tin oxide, and aluminum-doped zinc oxide; and non-oxidative compounds such as chalcogenides, lanthanum hexaboride, titanium nitride, and titanium carbide. Of these, tin-doped indium oxide (ITO) is preferable.

[0159] In addition, the transparent conductive film 52 of the film sensor 5 in the above-mentioned display devices 10A and 10B is located above the film sensor 5 in Figures 2 and 3, but this is not limited to this and may be located below the film sensor 5.

[0160] The protective panel 2 is a member for protecting the display module 7 of the displays 10A and 10B and other internal members from external factors, and is preferably made of a glass plate, a plastic plate, or a laminate containing these.

[0161] The glass plate is not particularly limited, and examples thereof include chemically strengthened glass, alkali-free glass, quartz glass, soda-lime glass, barium-strontium-containing glass, aluminosilicate glass, lead glass, borosilicate glass, barium borosilicate glass, etc. The thickness of the glass plate is not particularly limited, but is usually 0.1 to 5 mm, and preferably 0.2 to 2 mm.

[0162] The plastic plate is not particularly limited, and examples thereof include an acrylic plate, a polycarbonate plate, etc. The thickness of the plastic plate is not particularly limited, but is usually 0.2 to 5 mm, and preferably 0.4 to 3 mm.

[0163] A desired functional layer (hard coat layer, anti-glare layer, etc.) may be provided on one or both sides of the glass plate or plastic plate.

[0164] In the above display devices 10A and 10B, the transparent conductive film 3 is patterned and provided on the protective panel 2. The transparent conductive film 3 may be made of the same material as the transparent conductive film 52 of the above film sensor 5. Generally, one of the transparent conductive film 3 and the transparent conductive film 52 of the film sensor 5 forms a circuit pattern in the X-axis direction, and the other forms a circuit pattern in the Y-axis direction.

[0165] It is preferable that the display devices 10A and 10B according to the present embodiment do not have an anti-reflection layer, since the anti-reflection layer may reduce the hardness of the surface and may not provide the desired harmony in appearance.

[0166] When manufacturing the display device 10A, the release sheet 13 of the shatterproof adhesive sheet 1 may be peeled off and the exposed colored adhesive layer 12 may be attached to the front side of the protective panel 2 (the side on which the transparent conductive film 3 is not present), and then the display device 10A may be manufactured by a conventional method using the protective panel 2 with the shatterproof adhesive sheet 1. Alternatively, a display device (display device 10A without the shatterproof adhesive sheet 1 attached) may be manufactured by a conventional method, and then the shatterproof adhesive sheet 1 may be attached to the front side of the protective panel 2 (the side opposite the display module 7).

[0167] Furthermore, when manufacturing the display device 10B, the release sheet 13 of the shatterproof adhesive sheet 1 is peeled off, and the exposed colored adhesive layer 12 is attached to the transparent conductive film 3 provided on the back side of the protective panel 2, and then the display device 10B is manufactured by conventional methods using the protective panel 2 with the shatterproof adhesive sheet 1.

[0168] When the colored adhesive layer 12 is active energy ray curable, the shatterproof adhesive sheet 1 is attached via the colored adhesive layer 12 as described above, and then the colored adhesive layer 12 is irradiated with active energy rays. This causes the active energy ray curable component (C) in the colored adhesive layer 12 to polymerize, and the colored adhesive layer 12 is cured. The colored adhesive layer 12 may be irradiated with active energy rays through a member that transmits the active energy rays, for example, through the base material 11 of the shatterproof adhesive sheet 1.

[0169] The active energy ray refers to electromagnetic waves or charged particle rays having an energy quantum, and specific examples thereof include ultraviolet rays, electron beams, etc. Among active energy rays, ultraviolet rays are particularly preferred because they are easy to handle.

[0170] The ultraviolet irradiation can be performed by a high pressure mercury lamp, a fusion H lamp, a xenon lamp, etc., and the amount of ultraviolet irradiation is 50 to 1000 mW / cm illuminance. 2 It is preferable that the intensity is about 100 to 500 mW / cm 2 The light intensity is preferably about 50 to 10,000 mJ / cm. 2 is preferably 200 to 7000 mJ / cm 2 More preferably, it is 500 to 3000 mJ / cm 2 On the other hand, the irradiation with the electron beam can be carried out by an electron beam accelerator or the like, and the irradiation dose of the electron beam is preferably about 10 to 1000 krad.

[0171] Here, as shown in FIG. 4, the display bodies 10A and 10B according to the present embodiment preferably have a frame material 8 at the periphery of the display bodies 10A and 10B. The frame material 8 is preferably a dark or deep color such as black, brown, navy blue, purple, or blue, and is particularly preferably black. The color of the frame material 8, as defined by the CIE1976 L*a*b* color system, is preferably a lightness L* of 5 to 95, a chromaticity a* of -40 to 40, and a chromaticity b* of -40 to 40, and is particularly preferably a lightness L* of 10 to 80, a chromaticity a* of -30 to 30, and a chromaticity b* of -30 to 30, and is further preferably a lightness L* of 15 to 70, a chromaticity a* of -20 to 20, and a chromaticity b* of -20 to 20. The frame material 8 has such a color, and is therefore easily recognized by the human eye as a frame material with a high-class appearance. Furthermore, since the frame material 8 has the above-mentioned color, the colored adhesive layer 12 in this embodiment has a stronger sense of unity with the frame material 8, resulting in a better harmony in appearance.

[0172] In the above-mentioned display bodies 10A and 10B, the shatterproof adhesive sheet 1 having the colored adhesive layer 12 is attached to the protective panel 2, so that the appearance of the display body 10A and 10B matches well with the frame material 8 when the light is turned off, thereby improving the design. Even if the protective panel 2 is broken due to an impact or the like, the shatterproof adhesive sheet 1 attached to the protective panel 2 prevents the broken protective panel 2 from scattering.

[0173] The above-described embodiments are described for the purpose of facilitating understanding of the present invention, and are not described for the purpose of limiting the present invention. Therefore, each element disclosed in the above embodiment is intended to include all design modifications and equivalents that fall within the technical scope of the present invention.

[0174] For example, the release sheet 13 in the shatterproof adhesive sheet 1 may be omitted. In addition, another layer may be laminated on the surface of the substrate 11 opposite to the colored adhesive layer 12. Furthermore, another layer may be laminated between the substrate 11 and the colored adhesive layer 12. EXAMPLES

[0175] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples.

[0176] Example 1 1. Preparation of (meth)acrylic acid ester polymers 60 parts by mass of 2-ethylhexyl acrylate, 20 parts by mass of methyl methacrylate, and 20 parts by mass of 2-hydroxyethyl acrylate were copolymerized by solution polymerization to prepare a (meth)acrylic acid ester polymer (A). The molecular weight of this (meth)acrylic acid ester polymer (A) was measured by the method described below, and the weight average molecular weight (Mw) was 700,000.

[0177] 2. Preparation of adhesive composition 100 parts by mass (solid content equivalent; the same applies below) of the (meth)acrylic acid ester polymer (A) obtained in step 1 above, 0.2 parts by mass of trimethylolpropane-modified tolylene diisocyanate (manufactured by Toyochem Co., Ltd., product name "BHS8515") as a crosslinking agent (B), 0.5 parts by mass of a carbon black-based black pigment (C1) as a colorant (C), and 0.2 parts by mass of 3-glycidoxypropyltrimethoxysilane as a silane coupling agent were mixed, thoroughly stirred, and diluted with methyl ethyl ketone to obtain a coating solution of an adhesive composition.

[0178] Here, the formulations (solid content equivalent) of the pressure-sensitive adhesive composition when the (meth)acrylic acid ester polymer (A) is taken as 100 parts by mass (solid content equivalent) are shown in Table 1. The details of the abbreviations and the like shown in Table 1 are as follows. [(Meth)acrylic acid ester polymer (A)] 2EHA: 2-ethylhexyl acrylate MMA: Methyl methacrylate HEA: 2-hydroxyethyl acrylate BA: n-butyl acrylate AA: Acrylic acid MA: Methyl acrylate IBXA: Isobornyl acrylate ACMO: N-Acryloylmorpholine [Crosslinking agent (B)] TDI: Trimethylolpropane modified tolylene diisocyanate Epoxy: 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane Colorant (C) C1 to C2: Carbon black-based black pigments having the physical properties shown in Table 2 [Active energy ray-curable component (D)] ε-Caprolactone modified tris-(2-acryloxyethyl) isocyanurate [Photopolymerization initiator (E)] 2,4,6-Trimethylbenzoyl-diphenyl-phosphine oxide [Silane coupling agents] 3-Glycidoxypropyltrimethoxysilane [Ultraviolet absorber] 2,2-Dihydroxy-4-methoxybenzophenone

[0179] 3. Manufacturing of adhesive sheets As a coating liquid for forming an antiglare hard coat layer, 100 parts by mass (expressed as a solid content equivalent value; the same applies to other components below) of a polyfunctional (meth)acrylate (manufactured by Shin-Nakamura Chemical Co., Ltd., product name "NK Ester A-DPH"), 4.3 parts by mass of 1-hydroxycyclohexyl phenyl ketone as a photopolymerization initiator, 11 parts by mass of silica fine particles (manufactured by Fuji Silysia Chemical Co., Ltd., product name "Silo Hobic 702", average particle size 4.1 μm), 0.01 parts by mass of a leveling agent (manufactured by Dow Corning Toray Co., Ltd., product name "SH28"), and 8.3 parts by mass of silica nanoparticles (manufactured by Nissan Chemical Industries, Ltd., product name "MIBK-ST", average particle size: 10 nm) were mixed and diluted with propylene glycol monomethyl ether to prepare a coating liquid with a solid content concentration of 30%.

[0180] The above coating solution was applied to one side of a polyethylene terephthalate (PET) film (manufactured by Toray Industries, product name "125-U403", thickness 125 μm) using a Mayer bar #10 so that the film thickness after drying would be 1.5 μm, and the film was dried at 70° C. for 1 minute. Then, under a nitrogen atmosphere, a high-pressure mercury lamp was used to apply the coating with an illumination intensity of 200 mW / cm 2 , light intensity 300mJ / cm 2 The film was then exposed to ultraviolet light for 100 s to obtain a PET film (tensile modulus: 5.0 GPa, haze value: 4.0%) with an antiglare hard coat layer (AG-HC layer).

[0181] The adhesive composition coating solution obtained in step 2 was applied by a knife coater to the release-treated surface of a release sheet (manufactured by Lintec Corporation, product name "SP-PET752150"), one side of which was a polyethylene terephthalate film treated with a silicone-based release agent. Then, the coating was heated at 90°C for 1 minute to form a coating layer.

[0182] Next, the side of the PET film with an AG-HC layer described above opposite the AG-HC layer was laminated to the above coating layer, and the resulting film was cured for 7 days under conditions of 23°C and 50% RH to produce a shatterproof adhesive sheet consisting of a PET film with an AG-HC layer / colored adhesive layer (thickness: 25 μm) / release sheet.

[0183] The thickness of the colored adhesive layer is a value measured in accordance with JIS K7130 using a constant pressure thickness measuring instrument (manufactured by Techclock Corporation, product name "PG-02").

[0184] [Examples 2 to 9, Comparative Examples 1 to 3] A shatterproof adhesive sheet was produced in the same manner as in Example 1, except that the types and ratios of the monomers constituting the (meth)acrylic acid ester polymer (A), the weight average molecular weight (Mw) of the (meth)acrylic acid ester polymer (A), the type and amount of the crosslinking agent (B), the type and amount of the colorant (C), the amount of the active energy ray curable component (D), the amount of the photopolymerization initiator (E), the amount of the silane coupling agent, the amount of the ultraviolet absorber, and the thickness of the adhesive layer were changed as shown in Table 1. In Comparative Examples 1 to 3, an uncolored adhesive layer was formed. In Example 8, an active energy ray curable colored adhesive layer was formed, and in Comparative Example 2, an active energy ray curable adhesive layer was formed.

[0185] Example 10 100 parts by mass of an addition reaction type silicone resin (manufactured by Shin-Etsu Chemical Co., Ltd., "KS-847H"), 25 parts by mass of a silicone resin (manufactured by Toray Dow Corning Co., Ltd., "SD-4584"), 0.6 parts by mass of a platinum catalyst (manufactured by Toray Dow Corning Co., Ltd., "SRX 212 CATALYST"), 0.5 parts by mass of a carbon black-based black pigment (C2) as a colorant (C), and 50 parts by mass of methyl ethyl ketone as a diluent were mixed to obtain a coating solution of a silicone-based adhesive composition. Using the coating solution, a shatterproof adhesive sheet (having a colored adhesive layer made of a silicone-based adhesive) was manufactured in the same manner as in Example 1. However, the coating layer was formed by heat treatment at 130°C for 1 minute.

[0186] Comparative Example 4 A coating solution was prepared in the same manner as in Example 10, except that the colorant (C) was not added, and a shatterproof adhesive sheet (having an adhesive layer made of a silicone-based adhesive) was produced using the coating solution in the same manner as in Example 10.

[0187] Example 11 100 parts by mass of trifunctional polypropylene glycol (number average molecular weight 1000), 7 parts by mass of a trimethylolpropane adduct of tolylene diisocyanate, 0.01 parts by mass of dioctyltin dilaurate, and 43 parts by mass of toluene were charged and reacted for 3 hours at 100° C. Then, when the presence of isocyanate groups could no longer be confirmed by an infrared spectrophotometer, the mixture was cooled to obtain a polyurethane polyol solution.

[0188] 100 parts by mass of the obtained polyurethane polyol, 15 parts by mass of a trimethylolpropane adduct of tolylene diisocyanate, and 0.5 parts by mass of a carbon black-based black pigment (C2) as a colorant (C) were mixed, thoroughly stirred, and diluted with ethyl acetate to obtain a coating solution of a urethane-based adhesive composition. Using the coating solution, a shatterproof adhesive sheet (having a colored adhesive layer made of a urethane-based adhesive) was produced in the same manner as in Example 1. However, the coating layer was formed by heat treatment at 90°C for 1 minute.

[0189] Comparative Example 5 A coating solution was prepared in the same manner as in Example 11, except that the colorant (C) was not added, and a shatterproof adhesive sheet (having an adhesive layer made of a urethane-based adhesive) was produced using the coating solution in the same manner as in Example 11.

[0190] The weight average molecular weight (Mw) mentioned above is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC) under the following conditions (GPC measurement). <Measurement conditions> GPC measuring device: Tosoh HLC-8020 GPC columns (passed in the following order): Tosoh Corporation TSK guard column HXL-H TSK gel GMHXL (×2) TSK gel G2000HXL Measurement solvent: Tetrahydrofuran ·Measurement temperature: 40℃

[0191] [Test Example 1] (Measurement of total light transmittance) The total light transmittance (%) of the shatterproof adhesive sheets (with the release sheet already removed) obtained in the examples and comparative examples was measured using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., product name "NDH-5000") in accordance with JIS K7361-1:1997.

[0192] In addition, in the examples and comparative examples, a release sheet was laminated on the coating layer of the adhesive composition instead of the PET film with the AG-HC layer, and a measurement sample was prepared having a structure of release sheet / (colored) adhesive layer (thickness: 25 μm) / release sheet. The total light transmittance (%) of the (colored) adhesive layer in the obtained measurement sample was measured in the same manner as above. The respective results are shown in Table 3.

[0193] [Test Example 2] (Haze value measurement) The shatterproof adhesive sheets (with the release sheet already peeled off) obtained in the examples and comparative examples were measured for haze value (%) using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., product name "NDH-5000") in accordance with JIS K7136:2000. In addition, the (colored) adhesive layer in the measurement sample prepared in the same manner as in Test Example 1 was measured for haze value (%) in the same manner as above. The respective results are shown in Table 3.

[0194] [Test Example 3] (Measurement of L*a*b*) The shatterproof adhesive sheets (with the release sheet already peeled off) obtained in the examples and comparative examples were measured for lightness L*, chromaticity a*, and chromaticity b* as defined by the CIE1976L*a*b* color system using a simultaneous photometric spectrophotometer (manufactured by Nippon Denshoku Industries Co., Ltd., product name "SQ2000") in accordance with JIS K7136:2000. In addition, the lightness L*, chromaticity a*, and chromaticity b* of the (colored) adhesive layer in the measurement sample prepared in the same manner as in Test Example 1 were measured in the same manner as above. The respective results are shown in Table 3.

[0195] [Test Example 4] (Gel fraction) A measurement sample prepared in the same manner as in Test Example 1 was cut to a size of 80 mm x 80 mm, the (colored) adhesive layer was wrapped in a polyester mesh (product name: Tetoron mesh #200), and the mass was measured using a precision balance. The mass of the mesh alone was subtracted to calculate the mass of the adhesive alone. This mass was designated M1.

[0196] Next, the adhesive wrapped in the polyester mesh was immersed in ethyl acetate at room temperature (23°C) for 24 hours. The adhesive was then removed and air-dried for 24 hours in an environment with a temperature of 23°C and a relative humidity of 50%, and then dried in an oven at 80°C for 12 hours. After drying, the mass was weighed using a precision balance, and the mass of the adhesive alone was calculated by subtracting the mass of the mesh alone. The mass at this time was designated M2. The gel fraction (%) was expressed as (M2 / M1) x 100. The results are shown in Table 3.

[0197] [Test Example 5] (Measurement of image clarity) For the shatterproof adhesive sheets (with the release sheet already peeled off) obtained in the examples and comparative examples, an image clarity tester (manufactured by Suga Test Instruments, product name "ICM-10P") was used to measure the image clarity (%) of five types of optical combs (comb widths: 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm, and 2.0 mm) in accordance with the transmission method of JIS K7374:2007, and the total value was calculated. The results are shown in Table 3.

[0198] [Test Example 6] (Measurement of adhesive strength) The shatterproof adhesive sheets obtained in the Examples and Comparative Examples were cut into pieces 25 mm wide and 100 mm long to prepare samples.

[0199] The release sheet was peeled off from the sample in an environment of 23°C and 50% RH, and the exposed (colored) adhesive layer was attached to soda lime glass (manufactured by Nippon Sheet Glass Co., Ltd.), and then pressurized at 0.5 MPa and 50°C for 20 minutes in an autoclave manufactured by Kurihara Manufacturing Co., Ltd. Then, the sample was left for 24 hours under conditions of 23°C and 50% RH.

[0200] The shatterproof adhesive sheets of Example 7 and Comparative Example 2 were irradiated with active energy rays through the PET film with the AG-HC layer under the following conditions to cure the (colored) adhesive layer.

[0201] Next, the adhesive strength (N / 25mm) was measured using a tensile tester (manufactured by Orientec Co., Ltd., product name "Tensilon") at a peel speed of 300mm / min and a peel angle of 180 degrees. The measurements were performed under conditions other than those described here in accordance with JIS Z0237:2009. The results are shown in Table 3.

[0202] <Activated energy ray irradiation conditions> -Uses high pressure mercury lamp ·Illuminance 200mW / cm 2 ,Light intensity 2000mJ / cm 2 The UV illuminance and light intensity meter used is the "UVPF-A1" manufactured by Eye Graphics.

[0203] [Test Example 7] (Measurement of pencil hardness) The release sheet was peeled off from the shatterproof adhesive sheet obtained in the examples and comparative examples, and the exposed (colored) adhesive layer was attached to soda lime glass. The pencil hardness of the substrate surface (anti-glare hard coat layer surface) of the shatterproof adhesive sheet was measured using an electric pencil scratch hardness tester (manufactured by Yasuda Seiki Seisakusho, product name "No. 553-M1") in accordance with JIS K5600. The results are shown in Table 3.

[0204] [Test Example 8] (Evaluation of appearance harmony) The release sheet was peeled off from the shatterproof adhesive sheet obtained in the Examples and Comparative Examples, and the exposed (colored) adhesive layer was attached to soda lime glass (manufactured by Nippon Sheet Glass Co., Ltd., length 70 mm × width 70 mm × thickness 1.1 mm). A frame material (L*: 38.5, a*: -0.2, b*: 0.3) made of black resin plastic was attached to the periphery of the obtained laminate, and this was used as a sample.

[0205] The obtained sample was placed on a black printed paper background (L*: 29.8, a*: -0.7, b*: 0.6). The sample was then visually inspected under a three-wavelength fluorescent lamp (distance from the fluorescent lamp: 200 cm) to determine whether the frame material and the inner part of the frame material (corresponding to the display part of the display body) blended together (had a sense of unity), and the appearance harmony was evaluated according to the following criteria. The results are shown in Table 3. ⊚: The frame material and the display portion were very compatible with each other. ◯: The frame material and the display portion were blended together to some extent. ×: The frame material and the display portion clearly did not blend well together.

[0206] The color tone (L*a*b* defined by the CIE1976 L*a*b* color system) of the above frame material and black printed paper was measured using a spectrophotometer (manufactured by BYK, product name "Spectro-Guide").

[0207] [Test Example 9] (Evaluation of visibility) On a 15.6-inch display with a resolution of 1366 x 768 (manufactured by Fujitsu, product name "LITEBOOK A574 / H"), black text (font: MS P Gothic) on a white background was displayed at 100% in sizes from 5 point to 20 point (in 1 point increments).

[0208] A sample prepared in the same manner as in Test Example 8 was placed on the display. The size of the characters that could be visually recognized was confirmed at a position 50 cm from the display, and visibility was evaluated according to the following criteria. The results are shown in Table 3. ◎: 6 point characters were visible. ○: 6-point characters were not completely visible, but 8-point characters were visible. △: 8-point characters were not completely visible, but 15-point characters were visible. ×: 15 point characters were not visible.

[0209] [Test Example 10] (Evaluation of blackening ability) On a 15.6-inch display with a resolution of 1366 x 768 (manufactured by Fujitsu, product name "LITEBOOK A574 / H"), black text (font: MS P Gothic) on a white background was displayed at 50 point size at 100%.

[0210] A sample prepared in the same manner as in Test Example 8 was placed on the display. Then, at a position 50 cm from the display, the change in the blackness of the characters before and after the sample was placed was visually confirmed, and the blackness imparting ability was evaluated according to the following criteria. The results are shown in Table 3. ⊚: When the sample was placed, the blackness of the characters improved, making them easier to see. ○: When the sample was placed, the blackness of the characters was improved, but the background was dark and the characters were difficult to see. ×: The blackness of the characters did not change before and after sample placement.

[0211] [Test Example 11] (Evaluation of shatterproofness) The release sheet of the shatterproof adhesive sheet obtained in the examples and comparative examples was peeled off, and the exposed (colored) adhesive layer was attached to a soda lime glass plate (manufactured by Nippon Sheet Glass Co., Ltd.) having a length of 170 mm, a width of 150 mm, and a thickness of 1 mm. Then, a laminate consisting of the glass plate and the shatterproof adhesive sheet was placed on two tables having a height of 10 mm placed on a table. At this time, the shatterproof adhesive sheet side was facing upward (opposite the above-mentioned tables), and the laminate was placed so that the portions up to 10 mm from both ends in the long side direction were placed on the above-mentioned tables, and the center was placed in a floating state (height 10 mm). Then, an iron ball (200 g) having a diameter of 31.75 mm was dropped from a height of 30 cm onto the center of the laminate. The state of the laminate was then visually observed, and the shatterproofness was evaluated according to the following criteria. The results are shown in Table 3. ◯: The shatterproof adhesive sheet did not tear and the glass did not shatter. ×: The shatterproof adhesive sheet was torn and the glass was scattered.

[0212] [Table 1]

[0213] [Table 2]

[0214] [Table 3]

[0215] As can be seen from Table 3, products using the shatterproof adhesive sheets obtained in the examples had excellent appearance harmony with the frame material, and also had excellent character visibility, blackening ability, and shatterproof properties. [Industrial Applicability]

[0216] The shatterproof pressure-sensitive adhesive sheet of the present invention can be suitably used, for example, for displays that are required to blend in appearance with surrounding components when turned off, particularly for displays mounted on vehicles. [Explanation of symbols]

[0217] 1... Shatterproof adhesive sheet 11...Base material 12...Colored adhesive layer 13...Release sheet 2. Protective panel 3...Transparent conductive film 4...Adhesive layer 5. Film sensor 51...Base film 52...Transparent conductive film 6...Adhesive layer 7...Display module 8…Frame material 10A,10B…Display body

Claims

1. A shatterproof adhesive sheet provided on at least one surface side of a protective panel used in a display body, A substrate; A colored adhesive layer Equipped with The adhesive constituting the colored adhesive layer contains a colorant, an average haze, which is an average value of a haze value at a wavelength of 780 nm and a haze value at a wavelength of 380 nm, of a solution obtained by diluting the colorant by 10,000 times with ethyl acetate, is 1% or more and 20% or less; The content of the colorant is 0.01 parts by mass or more and 2 parts by mass or less with respect to 100 parts by mass of the adhesive base of the adhesive; The colorant is a pigment. A shatterproof adhesive sheet characterized by:

2. A shatterproof adhesive sheet provided on at least one surface side of a protective panel used in a display body, A substrate; A colored adhesive layer Equipped with The adhesive constituting the colored adhesive layer contains a colorant, The haze value of a solution obtained by diluting the colorant by 10,000 times with ethyl acetate at a wavelength of 780 nm is 0.1% or more and 20% or less, and The haze value of a solution obtained by diluting the colorant by 10,000 times with ethyl acetate at a wavelength of 380 nm is 1% or more and 20% or less, The content of the colorant is 0.01 parts by mass or more and 2 parts by mass or less with respect to 100 parts by mass of the adhesive base of the adhesive; The colorant is a pigment. A shatterproof adhesive sheet characterized by:

3. A shatterproof adhesive sheet provided on at least one surface side of a protective panel used in a display body, A substrate; A colored adhesive layer Equipped with The adhesive constituting the colored adhesive layer contains a colorant, an average haze, which is an average value of a haze value at a wavelength of 780 nm and a haze value at a wavelength of 380 nm, of a solution obtained by diluting the colorant by 10,000 times with ethyl acetate, is 1% or more and 20% or less; the pressure-sensitive adhesive is an acrylic pressure-sensitive adhesive containing a (meth)acrylic acid ester polymer (A), The (meth)acrylic acid ester polymer (A) contains, as a monomer unit constituting the polymer, 1% by mass or more and 35% by mass or less of a reactive group-containing monomer, The colorant is a pigment. A shatterproof adhesive sheet characterized by:

4. A shatterproof adhesive sheet provided on at least one surface side of a protective panel used in a display body, A substrate; A colored adhesive layer Equipped with The adhesive constituting the colored adhesive layer contains a colorant, The haze value of a solution obtained by diluting the colorant by 10,000 times with ethyl acetate at a wavelength of 780 nm is 0.1% or more and 20% or less, and The haze value of a solution obtained by diluting the colorant by 10,000 times with ethyl acetate at a wavelength of 380 nm is 1% or more and 20% or less, the pressure-sensitive adhesive is an acrylic pressure-sensitive adhesive containing a (meth)acrylic acid ester polymer (A), The (meth)acrylic acid ester polymer (A) contains, as a monomer unit constituting the polymer, 1% by mass or more and 35% by mass or less of a reactive group-containing monomer, The colorant is a pigment. A shatterproof adhesive sheet characterized by:

5. A shatterproof adhesive sheet provided on at least one surface side of a protective panel used in a display body, A substrate; A colored adhesive layer Equipped with The adhesive constituting the colored adhesive layer contains a colorant, an average haze, which is an average value of a haze value at a wavelength of 780 nm and a haze value at a wavelength of 380 nm, of a solution obtained by diluting the colorant by 10,000 times with ethyl acetate, is 1% or more and 20% or less; the pressure-sensitive adhesive is an acrylic pressure-sensitive adhesive containing a (meth)acrylic acid ester polymer (A), The (meth)acrylic acid ester polymer (A) contains 45 mass% or more of an alkyl (meth)acrylic acid ester as a monomer unit constituting the polymer, The colorant is a pigment. A shatterproof adhesive sheet characterized by:

6. A shatterproof adhesive sheet provided on at least one surface side of a protective panel used in a display body, A substrate; A colored adhesive layer Equipped with The adhesive constituting the colored adhesive layer contains a colorant, The haze value of a solution obtained by diluting the colorant by 10,000 times with ethyl acetate at a wavelength of 780 nm is 0.1% or more and 20% or less, and The haze value of a solution obtained by diluting the colorant by 10,000 times with ethyl acetate at a wavelength of 380 nm is 1% or more and 20% or less, the pressure-sensitive adhesive is an acrylic pressure-sensitive adhesive containing a (meth)acrylic acid ester polymer (A), The (meth)acrylic acid ester polymer (A) contains 45 mass% or more of an alkyl (meth)acrylic acid ester as a monomer unit constituting the polymer, The colorant is a pigment. A shatterproof adhesive sheet characterized by:

7. A shatterproof adhesive sheet provided on at least one surface side of a protective panel used in a display body, A substrate; A colored adhesive layer Equipped with The adhesive constituting the colored adhesive layer contains a colorant, an average haze, which is an average value of a haze value at a wavelength of 780 nm and a haze value at a wavelength of 380 nm, of a solution obtained by diluting the colorant by 10,000 times with ethyl acetate is 1% or more and 20% or less; the pressure-sensitive adhesive is an acrylic pressure-sensitive adhesive containing a (meth)acrylic acid ester polymer (A), The weight average molecular weight of the (meth)acrylic acid ester polymer (A) is 200,000 or more, The colorant is a pigment. A shatterproof adhesive sheet characterized by:

8. A shatterproof adhesive sheet provided on at least one surface side of a protective panel used in a display body, A substrate; A colored adhesive layer Equipped with The adhesive constituting the colored adhesive layer contains a colorant, The haze value of a solution obtained by diluting the colorant by 10,000 times with ethyl acetate at a wavelength of 780 nm is 0.1% or more and 20% or less, and The haze value of a solution obtained by diluting the colorant by 10,000 times with ethyl acetate at a wavelength of 380 nm is 1% or more and 20% or less, the pressure-sensitive adhesive is an acrylic pressure-sensitive adhesive containing a (meth)acrylic acid ester polymer (A), The weight average molecular weight of the (meth)acrylic acid ester polymer (A) is 200,000 or more, The colorant is a pigment. A shatterproof adhesive sheet characterized by:

9. The shatterproof adhesive sheet according to any one of claims 1 to 8, characterized in that the lightness L* defined by the CIE 1976 L*a*b* color system is 92 or less.

10. The shatterproof adhesive sheet according to any one of claims 1 to 9, characterized in that the total image clarity of optical combs of 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm and 2.0 mm measured in accordance with JIS K7374:2007 is 400 or more.

11. The shatterproof adhesive sheet according to any one of claims 1 to 10, characterized in that the total light transmittance is 5% or more and 95% or less.

12. The shatterproof adhesive sheet according to any one of claims 1 to 11, characterized in that the substrate is a plastic film having a functional layer.

13. A display body having a protective panel, The protective panel is provided on one or both sides with the shatterproof adhesive sheet according to any one of claims 1 to 12. A display characterized by:

14. 14. The display according to claim 13, further comprising a frame member on the periphery.

15. 15. The display according to claim 13, wherein a print layer is formed on a part of one of the display member constituting the display.

Citation Information

Patent Citations

  • Pressure-sensitive adhesive composition for attaching functional film and image display device

    JP2000313871A

  • Method of manufacturing electromagnetic wave blocking composite filter

    JP2009188298A

  • Optical filter and display device

    JP2012234028A

  • Adhesive sheet

    JP2017057375A

  • Adhesive sheet and display body

    JP2020007500A